Local Wisdom at Islamic Boarding Schools in Central Lombok 2023 - Syarifuddin, Syarifuddin; Iskandar, Muhammad Rozi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
National Islamic boarding school education, a very important link. This is not only because of the history of its emergence. But Islamic boarding schools have also significantly contributed to efforts to make the nation's life more intelligent. Historically, Islamic boarding schools are community-based educational institutions. Then it was developed by the community, so that the study of Islamic boarding schools as a center for community development. local wisdom in the Lombok cottage Tombok. With the following problem formulation: 1. What is local wisdom in Islamic boarding schools. 2 What are the forms of local wisdom that develop in Islamic boarding schools? Considering that this research is qualitative in nature, the data was collected through observation, interviews, documentation and data analysis methods. Based on research results, forms of local wisdom that developed in Islamic boarding schools in Central Lombok still exist. Namely the traditional tapsile procession of the Sasak tribe as principles, norms and rules of the social system of daily behavior that develop in society through an acculturative and contextual approach.